Fast bowling match workloads over 5–26 days and risk of injury in the following month. Issue 1 (January 2015) - Orchard, John W.; Blanch, Peter; Paoloni, Justin; Kountouris, Alex; Sims, Kevin; Orchard, Jessica J.; Brukner, Peter
Abstract Objectives This study examined whether high match fast bowling workloads in the short to medium term were associated with increased bowling injury rates. Design Prospective cohort study. Methods Over a 15 year period, workload patterns for 235 individual fast bowlers during time periods from 5 to 26 days were examined to consider whether there was an increased injury rate during the month (28 days) subsequent to the workload. Results Fast bowlers who bowled more than 50 match overs in a 5 day period had a significant increase in injury over the next month compared to bowlers who bowled 50 overs or less RR 1.54 (95% CI 1.04–2.29). For periods ranging from 12 to 26 days, there was no statistically-significant increase in injury over the next month from exceeding thresholds of certain amounts of overs, although bowlers who bowled more than 100 overs in 17 days had a non-significant increase in injury over the next month RR 1.78 (95% CI 0.90–3.50). Conclusion There were no statistically-significant increases in subsequent injury risk for high workloads for periods of 12–26 days, although exceeding 100 overs in 17 days (or less) was associated with higher injury rates. Compression of cricket fixtures is likely to have only a minimal contribution to increased fast bowling injury rates being seen in the T20 era (along with sudden workload increases due to transferring between forms of the game, which has been previously established as a major contributor).